FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN PERDAGANGAN, JASA DAN INVESTASI YANG TERDAFTAR DI ISSI - Nadia Laksmita Sari; Puji Sucia Sukmaningrum (Universitas Airlangga, 2019)
This research aims to find out the factors that influence company value (Tobin’s Q) trade, services and investment registered at ISSI during 2013-2017. This study uses a quantitative approach with panel data regression analysis techniques. The results of this study shows that managerial ownership, Return On Equity, Current Ratio, Debt To Asset Ratio, Total Assets Turnover Ratio simultaneously have a significant effect on firm value (Tobin’s Q). Partially managerial ownership variable has a significant negative effect, the Return On Equity variable has a positive significant effect, the Current Ratio and Debt To Asset Ratio variables have a positive insignificant effect and the Total Assets Turnover Ratio has a negative but not significant effect on firm value (Tobin’s Q).Keywords: Managerial Ownership, Return On Equity, Current Ratio, Debt to Asset Ratio, Total Asset Turnover Ratio, Tobin’s Q